2014
DOI: 10.3126/nje.v4i5.12023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Statins in Dyslipidemia: A Non interventional comparative study in a tertiary care hospital, Ajman, UAE

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Lipid profile is influenced by several factors including genetics, lifestyle and dietary factors [1] and although modifiable, dyslipidemia remains a leading risk factor for metabolic syndrome and cardiovascular disease such as coronary heart disease (CHD) [2,3]. According to World Health Organization (WHO), 4 million deaths are attributed to CHD worldwide per year [4], and 70% of patients with premature CHD symptoms demonstrate abnormal lipid metabolism. Earlier work has demonstrated that for every 10% reduction in serum total cholesterol (TC) levels, there is a 15% decline in CHD-linked mortality risk [5], highlighting the importance of dyslipidemia in CHD progression and the need to improve serum lipids in patients with dyslipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid profile is influenced by several factors including genetics, lifestyle and dietary factors [1] and although modifiable, dyslipidemia remains a leading risk factor for metabolic syndrome and cardiovascular disease such as coronary heart disease (CHD) [2,3]. According to World Health Organization (WHO), 4 million deaths are attributed to CHD worldwide per year [4], and 70% of patients with premature CHD symptoms demonstrate abnormal lipid metabolism. Earlier work has demonstrated that for every 10% reduction in serum total cholesterol (TC) levels, there is a 15% decline in CHD-linked mortality risk [5], highlighting the importance of dyslipidemia in CHD progression and the need to improve serum lipids in patients with dyslipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective 12-week study in 70 patients with newly diagnosed dyslipidemia in UAE showed the effectiveness of atorvastatin, simvastatin and rosuvastatin after 12 weeks of treatment (John et al, 2014). A cross-sectional study in Kuwait showed lower adherence to statin compared to the study reports from Canada and the US (Al-Foraih and Somerset, 2017).…”
Section: Figure 1: the Difference In Lipid Pro Ile At The Follow-up Vmentioning
confidence: 96%